Evaluation of the condition of the bottom of the tanks for petroleum products-forecast of the remaining operating life - Povše, Aleš (Strojniški vestnik, 2024)
Corrosion rate measurements in the tank enable us to develop a new model for predicting the remaining operating period of the tank. The empirical model for the study of bottom plate thicknesses and corrosion pits is more conservative than the standard linear model, as it considers the autocatalytic nature of the corrosion process. We used the double exponential distribution of maximum values (Gumbel's) to evaluate the maximum depth of pits, and the double exponential distribution of minimum values to evaluate the minimum values of the plate thickness. A comparison of the values of the parameters obtained using linear extrapolation and exponential models indicates the unreliability of linear extrapolation, since disregarding dynamic processes underestimates the actual rate of corrosion.
Keywords: corrosion models; časovno odvisna zanesljivost; dno rezervoarja za skladiščenje; korozijski modeli; luknjičasta korozija; pitting; storage tank bottom; time-dependent reliability